The Association of Raised Mid-trimester Serum Human Chorionic Gonadotrophin (hCG) and Alpha-Fetoprotein with adverse Pregnancy Outcome (Medico Legal Update, 2020)
Background: Placenta is a temporary endocrine organ formed during pregnancy, which produces hormonesimportant in the maintenance of a healthy pregnancy. hCG is the first one of these hormone that is measuredin pregnancy test and used in the follow up of adverse pregnancy outcome, Alpha fetoprotein is a majorplasma protein produced by the yolk sac and the fetal liver during fetal development.Aim of study :to studyrelationship between gestational complications and levels of maternal serum HCG and AFP and determinewhether the semarkers are effective predictors adverse pregnancy outcomes. Patients & Methods:Prospectivecohorts study in AlDiwaniyah maternity and pediatrics teaching hospital.We enrolled a total of 230 womenat 14-23 gestational weeks and measurement of maternal serum HCG & AFP were done, of those withnormal HCG & AFP formed (group l), group 2 involved women with elevated AFP , group 3 with elevatedHCG & group 4 involved women with elevated both HCG & AFP.Follow up weekly of the patients for thedevelopment of adversepregnancy outcome.Results: A significant relationship between adverse pregnancyoutcomes and abnormal elevation of HCG & AFP levels in the second trimester. In group 2 the patientsdeveloped higher rate of preterm labour & pre-eclampsia compared with the group 1. In group 3 with raisedHCG the rate of pre-eclampsia & IUGR development were higher than group 1. In group 4 with elevatedboth HCG & AFP higher incidence of pre-eclampsia & placental abruption , with a specificity(p